The mechanism of administration of a single social contribution and income tax for individuals: the advantages and problematic aspects of the implementation - Новицький, Андрій Миколайович; Чеховська, Ірина Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
There is analyzed the concept of «mechanism», defined the concept of «unification mechanism administration of a single social payment and physical body’s income tax». Defined structural elements of the unification mechanism administration of a single social payment and physical bodies’ income tax. Characterized the status of the Ministry of Revenue and Duties of Ukraine and its authority for administration of a single social payment and physical bodies’ income tax. Considered the European experience of administration of a single social payment and physical bodies’ income tax. Defined organizational and legal ways to ensure the administration of a single social payment and physical bodies’ income tax. Developed suggestions for the improvement of the unification mechanism administration of a single social payment and physical bodies’ income tax.